Research on cognitive reliability model considering crew influence in main control room of digital nuclear power plant - Xueyang Liu; Jianqiao Liu; Zhaoxu Meng; Jianjun Jiang (Scientific Reports)
Abstract Nowadays, human-system interaction way is gradually converted into digital way in large industry system. When an operator faces the change, cognitive process and reliability are also bound to change. For the situation, this paper proposed a Bayesian networks cognitive reliability model considering crew influence on human reliability. Based on traditional cognitive reliability influencing factors, this paper considered crew collaborative factors and analyzed cognitive phases. For each cognitive process and crew influence, the paper listed the influencing factors in detail and established a cognitive reliability model. For each cognitive process, corresponding calculation methods were presented based on Bayesian networks. Furthermore, by simulative analysis this proposed model had a good performance.In order to show the analysis process of proposed model, taking nuclear power plant as a background, an error probability about a safety injection(SI) scenario was quantitatively analyzed based on the proposed reliability model in this paper. The results of performance analysis and calculation process shown that the proposed model can be applied to nuclear power plant operator cognitive process evaluation.